If I had lived in Jesus' time - Graystone, Peter; Thomas, Jacqui (Nashville : Abingdon Press, 1995)
This book is designed to help children understand what life was like in Jesus' time in the first century A.D. Background information for adults is included.
Keywords: Bible -- Antiquities; Children -- Palestine; Palestine -- Civilization; Palestine -- Social life and customs